Tooth coronal index and pulp/tooth ratio in dental age estimation on digital panoramic radiographs—A comparative study. (August 2017) - Jain, Supreet; Nagi, Ravleen; Daga, Minal; Shandilya, Ashutosh; Shukla, Aastha; Parakh, Abhinav; Laheji, Afshan; Singh, Rahul
Highlights: The present study was undertaken with an aim to evaluate reliability of dental age assessment through two different methods for adults i.e. tooth coronal index and pulp/tooth ratio using digital panoramic radiographs and also to compare the methods for their accuracy in age determination. Digital panoramic radiographs of 180 subjects were analyzed of which 82 were males and 98 were females. Both PCTHR and TCI correlated negatively with chronological age. PCTHR showed slightly higher negative correlation and proved as a better tool for age estimation than TCI. Abstract: Background: Assessment of an age of an individual whether living or dead through teeth is one of the most reliable and simple method to calculate age than skeletal remains especially when they are in poor conditions. Objectives: The study was carried out with aim of (i) to evaluate reliability of dental age assessment through two different methods for adults i.e. tooth coronal index and pulp/tooth ratio using digital panoramic radiographs and (ii) to compare these methods for their accuracy in age determination. Materials and methods: The digital panoramic radiographs of 180 subjects of Chhattisgarh aged 15–70 years were selected for the study. The measurements were performed on the JPEG images of selected panoramic radiographs by using Adobe Acrobat 7.0 professional software. For tooth coronal index (TCI), height of the crown i.e. coronal height (CH) and the height of the coronal pulp cavity i.e. coronal pulp cavity height (CPCH) of mandibular second premolars and first molars was measured in millimeter (mm) and then TCI was calculated for each tooth and calculated age was compared with chronological age. For pulp/tooth ratio, the measurements of pulp chamber height (PCH) and crown root trunk height (CRTH) were performed on the mandibular first and second molar teeth, the pulp chamber crown root trunk height ratios (PCTHR) of selected tooth were calculated. The acquired data were subjected to Pearson correlation test, unpaired t test and Analysis of Variance (ANOVA) analysis. Results: Results suggested that TCI (mandibular first molar r = −0.178), second premolar (r = −0.187) and PCTHR(mandibular first molar r = −0.921, second molar r = −0.901) correlated negatively with chronological age suggesting decrease in size of pulp cavity. Mandibular first molar was found to be most reliable tooth to estimate dental age. Conclusion: The study showed that both PCTHR and TCI have negative association with chronological age. PCTHR showed slightly higher negative correlation and proved as a better tool for age estimation than TCI. Statistically significant differences were observed between chronological and calculated age by both methods thus emphasizing the need for future clinical trials.